2018
DOI: 10.1038/s41598-018-22177-0
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and dynamics of anti-CRISPR AcrIIA4, the Cas9 inhibitor

Abstract: The bacterial CRISPR-Cas system provides adaptive immunity against invading phages. Cas9, an RNA-guided endonuclease, specifically cleaves target DNA substrates and constitutes a well-established platform for genome editing. Recently, anti-CRISPR (Acr) proteins that inhibit Cas9 have been discovered, promising a useful off-switch for Cas9 to avoid undesirable off-target effects. Here, we report the solution structure and dynamics of Listeria monocytogenes AcrIIA4 that inhibits Streptococcus pyogenes Cas9 (SpyC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…Upon co-delivery of vectors encoding Cas9, sgRNA and Acr, the anti-CRISPR proteins will be made in parallel to Cas9 and the sgRNA. Due to the high affinity of Acrs to Cas9–sgRNA complexes (79,80), this switch design is tighter than the previous system (27). In fact, we showed that by increasing Acr vector doses, Cas9 activity in the OFF state can be pushed towards the detection limits of the used assays (Figures 2A–D, 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Upon co-delivery of vectors encoding Cas9, sgRNA and Acr, the anti-CRISPR proteins will be made in parallel to Cas9 and the sgRNA. Due to the high affinity of Acrs to Cas9–sgRNA complexes (79,80), this switch design is tighter than the previous system (27). In fact, we showed that by increasing Acr vector doses, Cas9 activity in the OFF state can be pushed towards the detection limits of the used assays (Figures 2A–D, 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CRISPR (Acr) proteins, i.e., naturally occurring CRISPR-Cas inhibitors (20,21), offer flexible strategies to regulate CRISPR-Cas activity and thereby to enhance the specificity of genome perturbations. Among these is AcrIIA4, a potent inhibitor of the Streptococcus pyogenes (Spy)Cas9 (22), which binds Cas9-sgRNA complexes with subnanomolar affinity (23) and impairs DNA targeting as well as nuclease function (24). Recent data show that administering AcrIIA4 shortly after SpyCas9-sgRNA delivery can reduce OFF-target editing (25), likely due to the slower editing kinetics at OFF-target sites as compared to perfect targets (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the pre-expressed AcrIIA4 completely inhibited cleavage by SpCas9 even when diluted by a factor of 100. Given that AcrIIA4 is known to act stoichiometrically by directly binding SpCas9 [15,55], these findings would suggest that the levels of preexpressed AcrIIA4 are at least 100-fold higher than those of either SpCas9 or the sgRNA.…”
Section: Resultsmentioning
confidence: 97%